Resposta :
x+x²=90
x²+x-90=0
b²-4.a.c
Delta=1²-4.1.(-90)
Delta=361
(Raiz de Delta=19)
x1=-b+raizdelta/2.a
x1=-1+19/2
x1=18/2
x1=9
x2=-1-19/2
x2=-20/2
x2=-10
As raizes da equação:
x1=9
x2=-10
substituindo na equaçao
9+(9)²=90
9+81=90
90=90
-10+(-10)²=90
-10+100=90
90=90
x²+x-90=0
b²-4.a.c
Delta=1²-4.1.(-90)
Delta=361
(Raiz de Delta=19)
x1=-b+raizdelta/2.a
x1=-1+19/2
x1=18/2
x1=9
x2=-1-19/2
x2=-20/2
x2=-10
As raizes da equação:
x1=9
x2=-10
substituindo na equaçao
9+(9)²=90
9+81=90
90=90
-10+(-10)²=90
-10+100=90
90=90
Resposta:
81+ 9
Explicação passo-a-passo:
Raiz quadrada de 81 é 9.
9+81= 90